Generation of energy from a pump functioning as a turbine in a main of water supply of Guanajuato - Joaquín Cuarenta, Jesús David; Mora Rodríguez, Jesús; Carreño Aguilera, Gilberto; Ortiz Medel, Josefina; Pérez-Sánchez, Modesto; López-Jiménez, Petra Amparo (Acta Universitaria, 2019)
In this work the characteristic curve of the operation of a pump as a turbine is obtained to calculate the energy that can be generated in a gravity pipeline from two dams to a drinking water treatment plant for water supply, which is supplied with a variable flow depending on consumption in the city of Guanajuato, Mexico. The characteristic curve is obtained by means of empirical formulas and experimental curves of pumps proposed by different authors, which predict the operation of the pump operating as a turbine. The formulas are used to determine the optimum operating point at which the machine can work, by means of the variables: flow rate, hydraulic head, and efficiency. In this case, the energy generated by the pump operating as a turbine is 90 626.35 kWh/year.